Metaphilosophy : philosophy in philosophical perspective - Rescher, Nicholas (Lexington Books, 2014)
Nicholas Rescher unites two facets of metaphilosophy to show that the historical perspective and forward-thinking normative, or systematic, approach are, together, an integral component of philosophy itself.